Effect of Educational Intervention of Clinical Librarian on Ophthalmology Assistants Skill in Usage of Evidence Based Medicine Information - Leila Keikha; Fatemeh Sheikhshoaei; Abdolahad Nabiolahi; Mahnaz Khosravi (پیاورد سلامت)
Background and Aim: Health librarians can play an important role in meeting the information needs of the clinical team and improving the quality of medical cares. Increasing clinical health literacy and use of Evidence-based medicine among ophthalmology residents is of great importance due to the importance of patients’ health in this field and appropriate decision-making about the individual’s health status. The present study aimed to evaluate the effect of an educational intervention by clinical librarians on the skills of ophthalmology residents in using of evidence-based information at Zahedan University of Medical Sciences. Materials and Methods: This was a semi-experimental applied study. The research population was ophthalmology residents of Al-Zahra Eye Hospital, Zahedan University of Medical Sciences during the years 2020-2023, who were selected through a census. During a three-month period, 17 combined training sessions (face-to-face and virtual using the Navid system) were held for 18 ophthalmology residents regarding correct search methods from different databases and appropriate use of evidence-based information. To collect data before and after training, a clinical information literacy questionnaire derived from previous studies was used, and data analysis was performed using SPSS software and ANOVA and ANCOVA statistical tests to compare scores before and after training in the intervention group. Results: The majority of participating residents (55.6%) were female. Before the intervention, 33.3% of the study population had moderate to high levels of knowledge about evidence-based medicine. There was a statistically significant relationship between the total level of knowledge of residents after training and gender (P-value<0.05). Clinical librarian training was effective on the level of basic knowledge of evidence-based medicine, designing clinical questions, searching for clinical evidence, critical evaluation of clinical evidence, and dissemination of evidence-based medical information of residents (P-value<0.05). Conclusion: Considering the positive impact of clinical librarians’ intervention in improving the level of clinical decision-making knowledge of ophthalmology residents, it is suggested that evidence-based medicine training workshops or courses be held for residents of different disciplines using a variety of educational methods. In addition, it is suggested that evidence-based units be included in the residents’ curriculum and that training be conducted as a team consisting of medical librarians and specialists and ophthalmologist.